Influence of Public Consciousness in Traditional Kazakh Society on Collective and Individual Legal Consciousness - ABDRASULOV, Ermek B.; GUBAIDULLIN, Murat G. (Journal of Advanced Research in Law and Economics, 2019)
The public consciousness of the people to a certain extent is formed due to the economic, cultural and political situation in which the ancestors lived. Their way of life, customs and traditions significantly affect future generations. The purpose of the article is to analyze the influence of the nomadic way of life on the public consciousness of traditional Kazakh society, the views of individual researchers on the formation of morals, character and actions of the Kazakhs in a nomadic civilization. The authors show the influence of customs and morality on the legal sphere of life, sense of justice of the traditional Kazakh society. As a result of the study, the influence of legal and other forms of social consciousness of nomadic life, their deed, lifestyle on the public consciousness of traditional Kazakh society is presented. Conclusions are made regarding general characteristics in terms of vital activity and lifestyle of nomadic tribes and the Kazakh tradition, as well as their relationship.